2008
DOI: 10.1016/j.pedhc.2007.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Quality of Life in Rural Children With Asthma and Their Parents

Abstract: Introduction-Among rural children with asthma and their parents, this study examined the relationship between parental and child reports of quality of life and described the relationship of several factors such as asthma severity, missed days of work and asthma education on their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 24 publications
1
25
0
5
Order By: Relevance
“…Therefore, Walker et al (2008) carried out a study in Maryland to examine the effects of school-based training on the QOL of the parents of school-age asthmatic children. Their findings indicated that their intervention significantly improved parents' knowledge, self-reliance, self-efficacy, endurance, confidence in healthcare system, ability to communicate with healthcare professionals, and QOL (8). Although most of the previous studies indicated the effectiveness of family-centered interventions in improving family caregivers' QOL, some studies reported that these interventions had no significant effects on QOL.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, Walker et al (2008) carried out a study in Maryland to examine the effects of school-based training on the QOL of the parents of school-age asthmatic children. Their findings indicated that their intervention significantly improved parents' knowledge, self-reliance, self-efficacy, endurance, confidence in healthcare system, ability to communicate with healthcare professionals, and QOL (8). Although most of the previous studies indicated the effectiveness of family-centered interventions in improving family caregivers' QOL, some studies reported that these interventions had no significant effects on QOL.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, due to its chronic nature, asthma affects parents' mental health and reduces their QOL (7). Walker et al (2008) found that parents' low QOL was significantly correlated with their children's absence from work and school, activity limitations, inadequate sleep, frequent nighttime awakenings, and poor psychological health (8). Empirical evidence shows that giving care to the children who suffer from chronic illnesses takes too much time and energy from the parents and hence, parents are compelled to allocate inadequate time to themselves and consequently suffer from poor QOL (9).…”
Section: Introductionmentioning
confidence: 99%
“…This inconsistency in results may be due to the different methods used to measure both asthma severity (e.g., parent's perception, clinician's assessment, diary ratings of symptoms, and examination of pulmonary function) and parents' QoL, as well as to the heterogeneity of the samples in terms of participants' variability across the spectrum of asthma severity. With regard to asthma's specific QoL impairments, the majority of studies using the PACQLQ measure have found a link between lower parental QoL and asthma severity according to asthma symptoms diaries (e.g., Stelmach et al, 2011), parents' reports of symptoms (e.g., Everhart et al, 2008;Walker et al, 2008) and symptom changes (e.g., Juniper et al, 1996). When clinical parameters such as pulmonary function are considered, the results are less clear, with some studies reporting weak correlations and others reporting no association with parents' QoL.…”
Section: Factors Influencing Qol Of Parents Of Children With Asthmamentioning
confidence: 99%
“…One mechanism through which uncontrolled asthma may affect parents' QoL is via its negative influence on the parental work domain, with research showing that parents with children with uncontrolled asthma missed more days at work than parents with children with controlled asthma (Dean et al, 2009). Additionally, parents' QoL scores were negatively linked to the number of missed days at work (e.g., Walker et al, 2008).…”
Section: Factors Influencing Qol Of Parents Of Children With Asthmamentioning
confidence: 99%
“…Studies by Cerdan, Alpert, Moonie, Cyrkiel, and Rue (2012), Silva, Crespo, Carona, and Canavarro (2015), and Walker et al (2008) also demonstrated an association between caregiver burden and caregiver QOL. Cerdan et al found that higher asthma severity in children, and the resulting increased burden of this, reflect lower PACQLQ scores and thus, lower QOL in caregivers (r = -0.34; p = 0.001).…”
Section: The Caregiver Context Of Disease: Factors Influencing Qolmentioning
confidence: 86%